Comparison of single and double pass friction stir welding of skin–stringer aviation aluminium alloy. (October 2013) - He, D; Yang, K; Li, M; Guo, H; Li, N; Lai, R; Ye, S
Abstract : To enhance the strength of the skin–stringer structures used in aircraft, comparative tests between single and double pass friction stir welding (FSW) were performed. Aluminium alloy was used for the skin (2524-T3, 1·8 mm) and stringer (7150-T77511, 2·4 mm). An equilateral right angled structure was used, and perfect joints without internal defects were obtained. Tensile, peel and metallographic tests were also implemented. The results show that the average peel strength of a double pass FSW joint is at least twice that from single pass FSW. Therefore, double pass FSW is an effective way of improving the connection strength of an aircraft skin–stringer structure.